Tryptophan 2,3-dioxygenase expression identified in human hepatocellular carcinoma cells and in intratumoral pericytes of most cancers - Hoffmann, D; Dvorakova, T; Stroobant, V; Bouzin, C; Daumerie, A; Solvay, M; Klaessens, S; Letellier, M-C; Renauld, J-C; van Baren, N; Lelotte, J; Marbaix, E; et al. (American Association for Cancer Research, 2019)
Tryptophan catabolism is used by tumors to resist immune attack. It can be catalyzed by indoleamine 2,3-dioxygenase (IDO1) and tryptophan 2,3-dioxygenase (TDO). IDO1 is frequently expressed in tumors and has been widely studied as a potential therapeutic target to reduce resistance to cancer immunotherapy. In contrast, TDO expression in tumors is not well characterized. Several human tumor cell lines constitutively express enzymatically active TDO. In human tumor samples, TDO expression has previously been detected by transcriptomics, but the lack of validated antibodies has precluded detection of the TDO protein and identification of TDO-expressing cells. Here we developed novel TDO-specific monoclonal antibodies and confirmed by immunohistochemistry the expression of TDO in the majority of human cancers. In all hepatocarcinomas (10/10), TDO was expressed by most tumor cells. Some glioblastomas (10/39) and kidney carcinomas (1/10) also expressed TDO in tumor cells themselves, but only in focal tumor areas. In addition, all cancers tested contained foci of non-tumoral TDO-expressing cells, which were identified as pericytes by their expression of PDGFRβ and their location in vascular structures. These TDO-expressing pericytes belonged to morphologically abnormal tumor vessels and were found in high-grade tumors in the vicinity of necrotic or hemorrhagic areas, which were characterized by neoangiogenesis. We observed similar TDO-expressing pericytes in inflammatory pulmonary lesions containing granulation tissue, and in chorionic villi, two tissue types that also feature neoangiogenesis. Our results confirm TDO as a relevant immunotherapeutic target in hepatocellular carcinoma, and suggest a proangiogenic role of TDO in other cancer types.